Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content1. The role of change approaches in security institutional excellenceDr. Sultan Abdulrahman Saif Al-Asm Al-Suwaidi2. The effectiveness of applying the accrual basis of accounting in the public sector in the Kingdom of Saudi ArabiaMrs. Jameelh Mohammed Al-Garni, Dr. Maha Faisal Al-Sayegh3. Training strategy and its impact on the performance of employees in Kuwaiti industrial companiesMrs. Fatima Abdulwahid Marafi4. The impact of sustainable development indicators on the consumption of renewable energy in the Kingdom of Saudi ArabiaDr. Vivian Mohammed Saleh Nasrulddin, Mrs. Khadijah Mohammed Abomadini, Mrs. Somaia Abdulrahman Al-Bishr, Mrs. Shrooq Mohammed Al-Zahrani5. Strategic changes adopted by Saudi National Center for Crisis and Health Disaster Management after Pandemic Covid-19Prof. Hasan Salih Al-Qudah, Mr. Nizar Abdulhai Al-Subahi, Dr.Mashael Ahmad Hobani6. The Cement Sector in Saudi Arabia between Challenges and Aspirations: An Analytical Study of the Cement Sector During the Period 2000 to 2021Mr. Ahmed Falah Aljohani7. Accounting Disclosure and Its Role in Attracting Foreign InvestmentsDr. Anwer Ata Ararawi
Keywords: Journal of Economic, Administrative and Legal Sciences